Pengaruh Pengungkapan Corporate Social Responsibility dan Enterprise Risk Managemen terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur tahun 2020) - Monica Shofiani; Sri Wibawani Wahyuni Astuti; Novitasari Agus Saputri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Many companies have stumbled on financial cases, the impact of which has resulted in a decline in the level of investor confidence so that it affects the value of the company. The value of the company reflects the assets owned by the company. Good CSR disclosure leads to higher consumer loyalty so that it has an impact on increasing sales. Every company whose company value is known must have company risk, the purpose of finding company value can lead to minimizing the company's risk that will be faced. This study aims to: 1) explain the effect of CSR disclosure on firm value, 2) explain the effect of ERM disclosure on firm value. The research subjects are 32 manufacturing companies listed on the Indonesia Stock Exchange 2020. CSR disclosure uses the Global Reporting Initiative 4 standard. ERM disclosure uses COSO 2017 guidelines. Firm value uses Price to Book Value. Data analysis using multiple regression with Stata version 16 program. The results obtained: 1) CSR has an effect on firm value. The existence of CSR disclosure affects the value of the company. The increase or decrease in the value of the company is influenced by the value of CSR. Investors can use CSR disclosure as the basis for making investment decisions so that CSR is considered to be profitable; 2) ERM has an influence on firm value. The existence of ERM disclosure has an effect on firm value. Investors use risk management information in making decisions to invest .